Answer:
A. Correct: When we plug in g(x) for the x in f(x), we get H(x).
B. Correct: When we plug in g(x) for the x in f(x), we get H(x).
C. Correct: When we plug in g(x) for the x in f(x), we get H(x).
D. Correct: When we plug in g(x) for the x in f(x), we get H(x).
Step-by-step explanation:
<em>Brainliest, please!</em>
Step-by-step explanation:
1. AB = BC (B is the midpoint of AC)
2. DE = EF (E is the midpoint of DF)
3. EB is common
4. ∠ABE = ∠CBE; ∠BED = ∠BEF (EB⊥AC, EB⊥DF)
5. ΔDEB ≅ ΔFEB (RHS)
6. DB = FB (corresponding ∠s of ≅ Δs)
7. ∠EFB = ∠CBF; ∠EDB = ∠ABD (alternate interior angles, AC║DF)
8. ΔABD ≅ ΔCBF (SAS)
Answer: he used incorrect time ratio
He incorrectly concluded that she is not running fast enough
Step-by-step explanation:
Answer:
you jus gotta be like me
Step-by-step explanation:
yuhhhhhhhhhh